Serotonin Subsystems Modulate Diverse and Opposite Behavioral Functions - Garcia Garcia, Alvaro L. (2019)
Pioneering work showed that serotonin (5-HT) neurons have the unique capacity to engage in different and opposed aspects of motivated behaviors such as reward and punishment responses. These findings provided strong evidence about the functional heterogeneity of 5-HT neurons, and their possible engagement in multiple and behaviorally distinct neural subsystems. A recent study provides further compelling evidence supporting this notion, in which two ascending 5-HT circuits modulate opposed aspects of motivated behaviors.